Enteral L-Arginine and Glutamine Supplementation for Prevention of NEC in Preterm Neonates - M. S. El-Shimi; H. A. Awad; M. A. Abdelwahed; M. H. Mohamed; S. M. Khafagy; G. Saleh (International Journal of Pediatrics)
Objective. Evaluating the efficacy and safety of arginine and glutamine supplementation in decreasing the incidence of NEC among preterm neonates. Methods. Prospective case-control study done on 75 preterm neonates ≤34 weeks, divided equally into L-arginine group receiving enteral L-arginine, glutamine group receiving enteral glutamine, and control group. Serum L-arginine and glutamine levels were measured at time of enrollment (sample 1), after 14 days of enrollment (sample 2), and at time of diagnosis of NEC (sample 3). Results. The incidence of NEC was 9.3%. There was no difference in the frequency of NEC between L-arginine and control groups (P>0.05). NEC was not detected in glutamine group; L-arginine concentrations were significantly lower in arginine group than control group in both samples while glutamine concentrations were comparable in glutamine and control groups in both samples. No significant difference was found between groups as regards number of septic episodes, duration to reach full oral intake, or duration of hospital stay. Conclusion. Enteral L-arginine supplementation did not seem to reduce the incidence of NEC. Enteral glutamine may have a preventive role against NEC if supplied early to preterm neonates. However, larger studies are needed to confirm these findings. This work is registered in ClinicalTrials.gov (ClinicalTrials.gov Identifier: NCT01263041).